PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES REVIEW UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STOIKIOMETRI DI KELAS X MIA SMA NEGERI 6 PEKANBARU - Shinta Arrum Sari; Betty Holiwarni; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to improve the achievement of learners on the subject of Stoichimetri in class X MIA SMAN 6 Pekanbaru. The research is a kind of experiment research with pretest-posttest design. Research conducted in SMAN 6 Pekanbaru. The samples of this research were the students of class X MIA 4 as the experimental class and students of class X MIA 3 as the control class randomly determined after the tests of normality and homogeneity test. The learning process at experimental class and control class based scientific approach to the curriculum in 2013. Experimental class is a class that is applied to Hollywood Squares Review method while the control class was not. Data analysis technique used is the t-test. Based on data analysis of significance value obtained 0,045<0,05, means that the use of Hollywood Squares Review method can improve student learning achievement on the subject of Stoichiometri in class X MIA SMAN 6 Pekanbaru.Keywords : Learning Achievement, Hollywood Squares Review, and Stoichiometric